Comparative analysis of intraoperative radiofrequency ablation versus non-anatomical hepatic resection for small hepatocellular carcinoma: short-term result - Yune, Yongwoo (Korean J Hepatobiliary Pancreat Surg, 2015)
BACKGROUNDS/AIMS: To compare the clinical outcomes of intraoperative radiofrequency ablation (RFA) and non-anatomical hepatic resection (NAHR) for small hepatocellular carcinoma (HCC). METHODS: From February 2007 to January 2015, clinical outcomes of thirty four patients with HCC receiving RFA or NAHR were compared, retrospectively. RESULTS: There was no difference of patient and tumor characteristic between the two groups that received RFA or NAHR. The 1, 2, and 3-year recurrence rates following RFA were 32.2%, 32.2% and 59.3% respectively, and 6.7%, 33.3% and 33.3% following NAHR respectively (p=0.287). The 1, 2 and 3-year overall survival (OS) rates following RFA were 100%, 88.9% and 76.2% respectively, and 100%, 85.6% and 85.6%, respectively, following NAHR (p=0.869). We did not find a definite statistical difference in recurrence rate and OS rate between the two groups. In the multivariate analysis, number of tumor was an independent prognostic factor for recurrence and albumin was an independent prognostic factor for OS. CONCLUSIONS: We recommend non-anatomical hepatic resection rather than intraoperative RFA in small sized HCC, due to a higher recurrence rate in intraoperative RFA. Intraoperative RFA was inferior to non-anatomical hepatic resection in terms of recurrence rate. We need to select the optimal treatment considering liver function and possibility of recurrence.